2011
DOI: 10.1007/s12015-011-9232-z
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells in Co-culture Enhance Embryonic Stem Cell Differentiation to Pancreatic Progenitors and Insulin-Producing Cells through BMP Signaling

Abstract: Endothelial cells (ECs) represent the major component of the embryonic pancreatic niche and play a key role in the differentiation of insulin-producing β cells in vivo. However, it is unknown if ECs promote such differentiation in vitro. We investigated whether interaction of ECs with mouse embryoid bodies (EBs) in culture promotes differentiation of pancreatic progenitors and insulin-producing cells and the mechanisms involved. We developed a co-culture system of mouse EBs and human microvascular ECs (HMECs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 53 publications
3
49
0
Order By: Relevance
“…The role of BMPs in pancreas development has also been explored previously [72,93] . We demonstrated that HMECs or mouse dermis as well as mouse AECs expressed BMPs and that BMP-2 and BMP-4 increased the phosphorylation levels of SMAD1,5,8 in pancreatic progenitors and beta-like cells derived from mouse ESCs [52,53,94] . These findings together with previous works pointed out the important role of ECs in beta-cell differentiation in vitro.…”
Section: Endothelium and Beta-cell Regeneration In Vivo And In Vitromentioning
confidence: 90%
See 4 more Smart Citations
“…The role of BMPs in pancreas development has also been explored previously [72,93] . We demonstrated that HMECs or mouse dermis as well as mouse AECs expressed BMPs and that BMP-2 and BMP-4 increased the phosphorylation levels of SMAD1,5,8 in pancreatic progenitors and beta-like cells derived from mouse ESCs [52,53,94] . These findings together with previous works pointed out the important role of ECs in beta-cell differentiation in vitro.…”
Section: Endothelium and Beta-cell Regeneration In Vivo And In Vitromentioning
confidence: 90%
“…Although some epithelial cells appeared, no cells derived from endoderm were identified [90] . Then, studies using co-cultures between human microvascular ECs (HMECs) and mouse EBs were performed [52,53,91] . In these studies, ECs from human dermis were able to induce differentiation of mouse EBs to pancreatic progenitors and insulin-producing cells [52] .…”
Section: Endothelium and Beta-cell Regeneration In Vivo And In Vitromentioning
confidence: 99%
See 3 more Smart Citations